Effect of manila palm (Veitchia merrillii Becc.) on rumen fermentation and microbial population in beef heifers - Tanitpan Pongjongmit; Thitima Norrapoke; Kampanat Phesatcha (CABI Agriculture and Bioscience)
Abstract The aim of the study was to evaluate the influence of manila palm (MP) on rumen fermentation and rumen microbial ecology in beef cattle. Four Brahman crossbred heifers with an initial body weight (BW) of 250 ± 40 kg (1–1.5 years old) were randomly assigned according to a 4 × 4 Latin square design to the following treatments: (1) Control (0% concentrate powder MP), (2) 1% concentrate powder MP, (3) 3% concentrate powder MP, and (4) 5% concentrate powder MP. The manila palm contained 12.54% of condense tannin. Cow were fed with a rice straw ad libitum and concentrate at 1%BW. There were no treatments effect on ruminal pH, NH3-N, microbial protein synthesis, nor ruminal temperature. Inclusion of MP did not affect (P > 0.12) blood urea N and hematocrit. However, ruminal concentration of acetic acid was linearly decreased (P < 0.01), while propionic acid was linearly increased (P < 0.01) as MP was increased in diet. In a such a manner that predicted ruminal CH4 production was decreased (P < 0.01) as MP was increased in diet. Inclusion of MP in diet decreased linearly (P = 0.02) protozoal population as MP level increased. The present study suggests that manila powder has modulatory effects on ruminal fermentation, decreasing acetate to propionate ratio, reducing estimated CH4 production without effects on ruminal pH, microbial synthesis nor blood parameters. Changes on ruminal fermentation parameters could be partially explained by decreases in the ruminal protozoa. Supplementation beyond 3% of concentrate portion (approximately 1.2% of total ration DM intake) did not increase significantly this positive effects, thus is recommended 1.2% of total ration as optimal use as an animal feed supplement.